Major cardiovascular adverse events in Fabry disease patients receiving agalsidase alfa - Ferrari, Gustavo (2021)
Cardiovascular mortality (CVM) has become the major contributor to overall Fabry disease (FD) mortality in the enzyme replacement therapy (ERT) era. Our objectives were to describe causes and potential predictors of mortality in FD adult patients in Argentina, and to assess risk of major adverse cardio vascular events (MACE) in the ERT era. We retrospectively studied 93 consecutive patients treated with alpha-galactosidase A (median follow up: 9.5 years from start of ERT). Mean age at ERT starting was 35±16.3 years. Prevalence of cardiomyopathy and renal disease reached 47% and 41%, respectively. Eleven subjects (11.8%, 95%CI: 5-18%) died during follow up (1.24/100 patient-years). Mean overall survival was 71 years (95%CI: 66-75 years). Seven cases were considered as CVM; main causes were sudden death and stroke. Risk of MACE was 14% (95%CI: 6.9-21.1%; 1.47 events/100 patient-years from start of ERT). All but 2 subjects had at least one comorbid cardiovascular risk factor; however, 86% of patients remained free of MACE during follow-up. CVM remained low and our study was underpowered for detection of predictors of mortality, but it is worth noting that age at diagnosis and ERT starting, left ventricular mass index and renal disease trended to correlate with CVM. Prevalence of hypertension, diabetes and dyslipidemia were lower in FD patients when compared to population level data. As in the Argentinean general population, CVM was the leading cause of mortality among this cohort of consecutive FD patients treated with agalsidase alfa.